Cultural turns : new orientations in the study of culture - Bachmann-Medick, Doris (De Gruyter, 2016)
"This book provides a comprehensive overview of cultural turns--ground-breaking theoretical reorientations in the study of culture, the humanities and the social sciences. It features chapters on the interpretive, performative, reflexice, postcolonial, translational, spatial and iconic turns while introducing emerging developments. This translation of an influential German classic--completely revised--is the first synthesis of cultural turns in the English-speaking world."